Effectiveness of low-cost air quality monitors for identifying volcanic SO₂ and PM downwind from Masaya volcano, Nicaragua - Whitty, Rachel; Pfeffer, Melissa; Ilyinskaya, Evgenia; Roberts, Tjarda; Schmidt, Anja; Barsotti, Sara; Strauch, Wilfried; Crilley, Leigh; Pope, Francis; Bellanger, Harold; Mendoza, Elvis; Mather, Tamsin; et al. (Volcanica, 2022)
Gas and particulate matter (PM) emissions from Masaya volcano, Nicaragua, cause substantial regional volcanic air pollution (VAP). We evaluate the suitability of low-cost SO2 and PM sensors for a continuous air-quality network. The network was deployed for six months in five populated areas (4-16 km from crater). The SO2 sensors failed and recorded erroneous values on multiple occasions, likely due to corrosion, requiring significant maintenance commitment. The PM sensors were found to be robust but data required correction for humidity. SO2 measurements could not be used as stand-alone tools to detect occurrence of VAP episodes (VAPE), but SO2/PM correlation reliably achieved this at near-field stations, as confirmed by meteorological forecasts and satellite imagery. Above-background PM concentrations reliably identified VAPE at both near-field and far-field stations. We suggest that a continuous network can be built from a combination of low-cost PM and SO2 sensors with a greater number of PM-only sensors.
Keywords: Nobert_Sebastien